2019
DOI: 10.3892/ol.2019.9899
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prior antibiotic use on the efficacy of nivolumab for non‑small cell lung cancer

Abstract: Gut microbiota serves an important role in shaping systemic immune responses. Antibiotics cause changes in the gut microbiota that may influence the efficacy of cancer immunotherapy. In the present study, a retrospective analysis of the data from 90 patients treated with nivolumab for non-small cell lung cancer (NSCLC) was conducted. A total of 13 patients were treated with antibiotics prior to nivolumab therapy. The median progression-free survival time in patients treated with antibiotics was 1.2 months [95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 44 publications
6
92
2
2
Order By: Relevance
“…In contrast, two retrospective reviews reported negative findings, with antibiotic use not influencing responses to nivolumab in patients with lung cancer .…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, two retrospective reviews reported negative findings, with antibiotic use not influencing responses to nivolumab in patients with lung cancer .…”
Section: Discussionmentioning
confidence: 94%
“…Among the publications retrieved using electronic search, 15 studies were eligible for quantitative analysis, for a total of 2,363 patients [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, two studies [23,24] were prospective (labeled with *). Across all studies, it clearly demonstrated that only antibiotic exposure within 2 months prior to the initiation of ICIs universally exhibited negative impact on treatment response of ICIs (Figure 4b and c), except one study [10] (Supplemental Figure 3).…”
Section: The Potential Impact Of Antibiotics On the Therapeutic Effecmentioning
confidence: 95%
“…However, several key questions remain to be addressed: 1) whether there is shared feature of gut microbiome that links to ICI response and AEs across various solid tumors; 2) whether antibiotics can affect cancer immunotherapy. This is important considering there are controversial results [6,9] , [10,11], and antibiotic is such an inevitable gut microbiome modi er in the clinical setting; 3) whether diet, as one of the most important lifestyle factors, will have impact on cancer immunotherapy. We aim to investigate existing evidence that could help address these questions at the human level using a systematic review.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation